Splenic Gestation: A rare case report - Patil, Narendra Ramrao; Birare, Shivaji Dadarao; Dale, Apurva Ravindra; Mahule, Sanjay Khemlal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Abdominal ectopic pregnancy accounts for only 1.3% of all ectopic pregnancies and occurs when a fertilised ovum implants in an extra pelvic peritoneal location. Splenic pregnancy is one of the least common form of abdominal ectopic pregnancy. Early diagnosis is essential as delay in treatment carries significant potential for morbidity and mortality. We present a case of 22-year-old female with 6 weeks amenorrhoea and acute abdomen. Patient underwent emergency exploratory laparotomy with suspicion of ?splenic hemangioma ?ruptured ectopic pregnancy. Splenectomy was performed. Final diagnosis was confirmed on histopathology showing chorionic villi invading the splenic parenchyma.